Fiasco : The American Military Adventure in Iraq - Ricks, Thomas E. (GHQ, Rawalpindi Services Book Club, 2009)
Fiasco is a masterful reckoning with the planning and execution of the American military invasion and occupation of Iraq through mid-2006, now with a postscript on recent developments. Ricks draws on the exclusive cooperation of an extraordinary number of American personnel, including more than one hundred senior officers, and access to more than 30,000 pages of official documents, many of them never before made public. Tragically, it is an undeniable account$1 (Bexplosive, shocking, and authoritative$1 (Bof unsurpassed tactical success combined with unsurpassed strategic failure that indicts some of America's most powerful and honored civilian and military leaders.s
Includes Index, Notes, Map and Abbreviations.
Keywords: Iraq War (2003-2011) -- Iraq